Application of Sargassum muticum as a nature-based fertilizer to enhance the growth of Capsicum annuum L. plants - Oumaima Ouala; Yasser Essadki; El Mahdi Redouane; Ouafa Cherifi; Fatima El Khalloufi; Brahim Oudra (Journal of Taibah University for Science)
Macroalgae, based on their content in bioactive molecules, are solicited for sustainable crop production. This study explores the use of Sargassum muticum from Moroccan coasts, as a biofertilizer for Capsicum annuum L. The biochemicals and mineralogical characterization of S. muticum confirmed its richness in protein, sugar, nitrogen, macro- and micro-elements. Thus, biomass analysis revealed the presence of indole-3-butyric acid (IBA) at 0.14 mg. g−1. C. annuum were exposed to 5, 20, and 30 g. kg−1 of S. muticum and were compared to controls. Results showed improvements in plant growth parameters. Photosynthetic activity, minerals, protein, and total sugar content, were also enhanced mainly with 20 g. kg−1. The fruits nutritional yield was significantly improved. Nitrogen, phosphorus, and potassium contents were of 95.2, 136.8, and 639.2 mg·g−1 dry weight. The obtained results encourage the application of S. muticum as an environmentally friendly biofertilizer for promoting sustainable crops, and reducing the adverse effects of conventional chemical fertilizers.